Influencing knowledge workers: The power of top management - Jayasingam, Sharmila Jayasingam; Jantan, Muhamad; Ansari, Mahfooz A.; Raman, Kavitha (2008)
Leadership is known as the major factor that can influence and motivate knowledge workers to contribute and participate actively in creating, sharing and using knowledge effectively. A survey of 180 Multimedia Super corridor(MSC) status firms was conducted to identify what leadership characteristics (in the form of social power) are needed in a knowledge-based firm.The results showed that knowledge leaders should embrace personal power and avoid information power.Position power must be exercised with caution because it not only encourages knowledge sharing but also impedes knowledge acquisition.Careful use of power can successfully influence k-workers to apply knowledge management practices (KMP).